KAJIAN MENGENAI PENGARUH PENANAMAN MODAL ASING LANGSUNG TERHADAP PERTUMBUHAN EKONOMI DAN TABUNGAN DOMESTIK INDONESIA TAHUN 1969-1994 - Basuki Soelistyo (Faculty of Economics and Business, Universitas Gadjah Mada, 1997)
The objectives of mis study are: (1). to identify factors affecting the foreign direct investment (FD1) inflows into Indonesia; (2). to analyze the effects of FDI on the Indonesian economic growth (GR); and (3). to analyze the effects of the FDI on the Indonesian domestic saving (SA V). The research used time series data for 27years, from 1969 to 1994.The study used two models: (1). linear multiple regression model, and (2). a simultaneous equation system model using two equations: growth and savings equationThe estimation was completed with test of classical asumptions, test for parameter stability, test for functional form and the Granger Causality Test As a result, the effects of per capita gross domestic product (GDPN), the share of manufacturing industry in Indonesian gross domestic product (SHARE), the availability of infrastructures (INF), economic growth (GR), the availability ofstalled labor (EDLAB), the exchange rate (IEXQ, and the tax incentive (TAX) on the FDI inflows into Indonesia was positive, but the effect ofInternational interest rates (LIBOR) on the FDI inflows into Indonesia was negative. The effects of foreign aid (AID), FDI, and the growth of labor force (CLF) on GR were positive. The effects of SA V and export performance (CX) on growth were insignificant The effects of AID, FDICX, and GDPN on SA V was positive, but the effect of GR on SAV was insignificant. According to the related criteria, the models formulated above are statistically good predictors. Based on the Granger Causality test, the GR and theSAV were independent The Indonesian economic growth is driven more by FDI and AID compared to domestic savings; and the economic growth is more absorbed into consumption activities compared to savings activities.